1977
DOI: 10.1007/bf02256463
|View full text |Cite
|
Sign up to set email alerts
|

Colonic ileus

Abstract: Nine cases of colonic ileus, characterized by selective or disproportionate distention of the large intestine without organic obstruction, are detailed. Massive cecal dilatation often dominates the radiographic presentation and may portend perforation. While management is generally conservative, cecostomy may be necessary to prevent peritonitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1983
1983
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 16 publications
(18 reference statements)
0
3
0
1
Order By: Relevance
“…This finding should nonetheless be considered indicative of a long-standing stenosis, and it is due to excessive bacterial proliferation with progressive distension of the intestinal lumen [27][28][29].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This finding should nonetheless be considered indicative of a long-standing stenosis, and it is due to excessive bacterial proliferation with progressive distension of the intestinal lumen [27][28][29].…”
Section: Discussionmentioning
confidence: 96%
“…Il riscontro di tale alterazione deve, comunque, essere considerato significativo di una stenosi protratta nel tempo ed è riferibile ad una eccessiva proliferazione batterica, responsabile di una progressiva distensione del lume intestinale [27][28][29].…”
Section: Discussionunclassified
“…Conservative management is successful as the primary treatment in the majority of patients. [14][15][16][17][18][19] Sloyer et al reported 25 cancer patients with ACPO (mostly nongastrointestinal malignancies). 14 The mean cecal diameter was 11.7 cm (range 9-18 cm).…”
Section: Supportive Therapymentioning
confidence: 99%
“…Conservative management is successful as the primary treatment in the majority of patients 11–17 . Sloyer et al .…”
Section: Managementmentioning
confidence: 99%